The Effect of Exercise Program on Low Back Pain Preventive Behaviors in Pregnant Females Referred to Health Centers of Karaj - Maryam Khalednejad; Sedighe Tavafian; Shamsodin Niknami (Hamadan University of Medical Sciences, 2016)
Background and Objectives: Back pain is the most common pain in pregnancy. This research aimed at exploring the influence of exercise program training on behavior change that leads to back pain prevention in pregnant females. Materials and Methods: This research was semi-experimental with pretest-post-test and control group research method, and included 120 pregnant females that referred to the Karaj Health Center. These females were selected randomly and divided to 2 groups, including control (60 persons) and intervention (60 persons). The research used 3 tools, the demographical questionnaire, Visual Analogue Scale (VAS), and awareness and attitude questionnaire, in order to specify back pain preventive behavior. Data were then analyzed using SPSS 21 with the paired t-test, Mann-Whitney, and Tukey tests. Results: There were significant differences between average awareness, attitude and preventive behaviors, and rate of back pain in the third trimester of pregnancy in the intervention group before and after the intervention (P >0.05). Also, there was a significant difference in the mentioned items between the intervention and control groups (P >0.05). Conclusions: This research showed that the training intervention could improve awareness, attitude, and behavior of pregnant females in back pain prevention.